Profil Kromatografi Lapis Tipis (KLT) dan Uji Aktivitas Antifungi Ekstrak n-Heksan Herba Kembang Bulan (Tithonia diversifolia (Hemsl.)Gray) Terhadap Candida albicans dan Microsporum canis - Heny Kurniasari; Andi Josep Nicolas Hutahaean; Uly Widya Rochmatil Ulla; Tumpal Manurung (Herbal Medicine Journal, 2022)
Moon flower herb is a well-known plant species that has been used as traditional medicine in Indonesia for generations. In previous studies it was known that moonflower (Tithonia diversifolia (Hemsl) Gray) had antihyperglycemic, antidiabetic, antimicrobial and antimalarial effects. Based on previous research, it is also known that the roots, stems, leaves and essential oil of moonflower (Tithonia diversifolia (Hemsl) Grey) contain alkaloids, phenolic compounds, steroids, saponins and flavonoids. The purpose of this study was to determine the activity of n-Hexan of moonflower herb against Candida albicans and Microsporum canis. This research was conducted in several stages, starting with the process of collecting and processing samples, testing the characteristics of simplicia, and maceration. Moonflower herb extract (Tithonia diversifolia (Hemsl) Grey, Thin Layer Chromatography (TLC) and antifungal activity testing. The results showed that moonflower herbs had a moisture content of about 10.2%. Thin Layer Chromatography (TLC) tested moonflower herbs against n-hexane extract containing polyphenolic compounds and steroids.The minimum inhibitory concentration (MIC) of n-hexane extract of moonflower herb against Candida albicans ATCC 10231 was at a concentration of 400 mg/mL which was 7.8 mm, while Microsporum canis at a concentration of 200 mg /mL is 7.28 mm.